Microalgal-based biopolymer for nano- and microplastic removal: a possible biosolution for wastewater treatment - Cunha, César (2021)
The increasing water pollution caused by the presence of nano- and microplastics has shown a need to pursue solutions to remediate this problem. In this work, an extracellular polymeric substance (EPS) producing freshwater Cyanothece sp. strain was exposed to nano- and microplastics. The bioflocculant capacity of the biopolymer produced was evaluated. The influence of different concentrations (1 and 10 mg L-1) of polystyrene nano- and microplastics in the extracellular carbohydrates and in the EPS production was studied. The presence of nano- and microplastics induced a negative effect on the microalgal growth (of up to 47%). The results show that the EPS produced by Cyanothece sp. exhibits high bioflocculant activity in low concentrations. Also, the EPS displayed very favourable characteristics for aggregation, as the aggregates were confirmed to consist of microalga, EPS and both the nano- and microplastics. These results highlight the potential of the microalgal-based biopolymers to replace hazardous synthetic flocculants used in wastewater treatment, while aggregating and flocculating nano- and microplastics, demonstrating to be a multi-purposed, compelling, biocompatible solution to nano- and microplastic pollution.